Taxonomic re-evaluation of the subspecies of Hebius vibakari (Boie, 1826) (Reptilia: Serpentes: Natricidae), with new evidence from central and northern China - Gao, Zong-Yuan; Huang, Jun-Jie; Ding, Li; Jiang, Ke; Mao, Jie; Ren, Jin-Long (Zootaxa, 2024)
Hebius vibakari (Boie, 1826), the type species of the genus Hebius, currently includes three subspecies: Hebius vibakari vibakari, endemic to Japan except for the Hokkaido region; Hebius vibakari ruthveni (Van Denburgh, 1923), found in the Korean Peninsula, northeastern China, and eastern Russia; and Hebius vibakari danjoensis (Toriba, 1986), native to the Oshima Island, Danjo Islands, Japan. However, the taxonomic status of three subspecies has not been evaluated for many years. Integrating data from previous studies and new records from central and northern China, we evaluated the systematic positions of H. v. vibakari and H. v. ruthveni based on comparative morphology and molecular phylogenetics. Analysis recovered H. vibakari as a monophyletic group, composed of three major clades that could not correspond to the nominative subspecies. As molecular and morphological evidence could not distinguish H. v. ruthveni from H. v. vibakari, we synonymized the junior nomen H. v. ruthveni with H. v. vibakari. A detailed description of Hebius vibakari is provided, including hemipenial morphology, and the taxonomic status of the subspecies H. v. danjoensis is discussed.